Pelaksanaan Kegiatan Tadarus Al-Qur’an dalam Menumbuhkan Minat Membaca Al-Qur’an Anggota Rohis di SMK Negeri 1 Wonosobo - Indriyani Indriyani; Ahmad Zuhdi; Salis Irvan Fuadi (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
This research aims to determine how the implementation of the Al-Qur'an reading activities in cultivating the interest of reading the Al-Qur'an among the members of Rohis at SMK Negeri 1 Wonosobo. To identify the problems in this study, the author uses a descriptive qualitative research methodology with field research type. The results of this study show that: 1) The implementation of the Al-Qur'an reading activities in extracurricular has been quite good, this activity is conducted once a month with the division of 1 juz per person. 2) In relation to the implementation of the Al-Qur'an reading activities in the Rohis extracurricular, fostering the reading interest of the Al-Qur'an among Rohis members at SMK Negeri 1 Wonosobo, this is evidenced by the fact that not a few Rohis members have been consistent in reading the Al-Qur'an. Initially, they only read 3 or 4 times a week, but after participating in the Al-Qur'an reading activities, they now read the Al-Qur'an every day. 3) For the internal hindrances, they lie in the varying abilities of Rohis members in reading the Al-Qur'an, which means that some children are still not fluent in their reading and have not yet mastered the rules of Tajweed. Meanwhile, the external hindering factors include several extracurricular activities that take place at the same time as the Rohis extracurricular activities, and other obstacles include the need for a special Rohis coach to teach Reading and Writing the Qur'an (BTQ). The supporting factors for this activity are adequate school facilities, a positive and motivating environment.